Si composite materials for use in lithium-ion battery anodes and methods for their preparation - Patents.com

Si composite materials with a core-shell structure and cyclized PAN binders stabilize silicon anodes, improving conductivity and energy density in Li-ion batteries.

JP2024546890APending Publication Date: 2024-12-26NOHMS TECH INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024535649
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-16
Filing Date
2022-12-16
Publication Date
2024-12-26

AI Technical Summary

Technical Problem

Existing Li-ion batteries face challenges in achieving high energy density due to material instability of pure silicon anodes when exposed to electrolytes, necessitating improved Si-based anode materials with enhanced stability and conductivity.

Method used

The use of Si composite materials, such as Si-carbon composites, with a core-shell structure and a cyclized polymeric binder, such as cyclized polyacrylonitrile (PAN), to stabilize silicon particles and enhance conductivity, along with conductive carbon particles and a fluorinated carbonate electrolyte.

Benefits of technology

The Si composite materials with cyclized PAN binders provide improved mechanical stability and conductivity, addressing the material instability of pure silicon anodes, thereby enhancing the energy density and cycle life of Li-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024546890000001_ABST
    Figure 2024546890000001_ABST
Patent Text Reader

Abstract

Disclosed are an anode formulation containing a plurality of active Si composite material particles, a plurality of conductive carbon particles, and at least one polymer binder that undergoes a cyclization reaction when heated; an anode formed from the anode formulation; a method of making the anode; and an electrochemical energy storage device comprising the anode, a cathode, and an electrolyte comprising a fluorinated carbonate.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] cross reference This application claims the benefit of the filing date of U.S. Provisional Patent Application No. 63 / 290,273, filed December 16, 2021, which is incorporated by reference herein in its entirety.

[0002] The present disclosure relates to silicon (Si)-based anodes for improving conductivity, specific capacity, and cycle life stability, and methods for producing high-capacity Si-based anodes suitable for use in electrochemical energy storage devices. More specifically, the present disclosure relates to the use of Si composite materials, such as silicon-carbon composite materials, silicon oxides, and the like, as active material particles in Li-ion battery anodes. [Background technology]

[0003] Lithium-ion (Li-ion) batteries are used in large quantities in consumer electronics, electric vehicles (EVs), energy storage systems (ESSs), and smart grids. The energy density of Li-ion batteries depends, at least in part, on the anode and cathode materials used. Optimization of Li-ion battery processing and manufacturing has allowed for a 4-5% improvement in the energy density of Li-ion batteries each year, but these incremental improvements are not sufficient to reach the energy density targets of next generation technologies. Reaching such targets will require advances in electrode materials, such as the incorporation of high energy density active materials within the electrodes. Recent research has focused primarily on the development of high energy cathodes, with only limited work devoted to the development of anode materials.

[0004] Recently, silicon has emerged as one of the most attractive high-energy anode materials for Li-ion batteries. Silicon's low working voltage and high theoretical specific capacity of 3579 mAh / g are nearly 10 times that of traditional graphite, thus bringing more interest. U.S. Patents 10,573,884 and 10,707,481 describe an anode composition containing silicon active material particles and a polymer binder such as polyacrylonitrile (PAN). The silicon active material particles described in the '884 and '481 patents are pure silicon particles with sizes in the nano to micron range. Also, an ionic liquid-based electrolyte was required.

[0005] One challenge faced by anode materials containing pure silicon as active material is the material level instability of pure silicon. For example, when pure silicon is used as the active material of the anode, it comes into direct contact with and is exposed to the electrolyte used therewith. This can lead to instability of the anode and the battery. Therefore, there is a need for improved Si-based anode materials for Li-ion batteries. Summary of the Invention

[0006] According to one aspect of the present disclosure, there is provided an anode formulation for forming an anode for use in an electrochemical energy storage device, the anode formulation comprising: a plurality of active Si composite material particles, a plurality of conductive carbon particles; and at least one polymer binder that undergoes a cyclization reaction when heated.

[0007] According to another aspect of the present disclosure, there is provided an anode for use in an electrochemical energy storage device, the anode comprising an active Si composite material, conductive carbon, and a current collector having a coating comprising at least one cyclized polymer binder.

[0008] According to another aspect of the present disclosure, there is provided an electrochemical energy storage device comprising: an anode comprising a current collector having a coating comprising an active Si composite material, conductive carbon, and at least one cyclized polymer binder; a cathode; and an electrolyte comprising a fluorinated carbonate.

[0009] According to another aspect of the present disclosure, there is provided a method of making an anode for use in an electrochemical energy storage device, comprising: a) mixing together active Si composite particles, conductive carbon particles, and at least one polymer binder that undergoes a cyclization reaction when heated to form a mixture; b) coating the mixture onto a current collector to form a coated current collector; and c) subjecting the coated current collector to a temperature treatment to cyclize the at least one polymeric binder. A method is provided that includes:

[0010] These and other aspects of the technology described herein will become apparent after consideration of the detailed description and claims appended hereto. [Brief description of the drawings]

[0011] [Figure 1] 1 is a flow diagram illustrating a method of making an anode comprising Si composite particles according to various embodiments described herein. [Figure 2A] FIG. 1 is a photograph showing an anode electrode prepared with polyvinylidene fluoride (PVDF) binder from a full pouch cell, where substantial swelling was observed and the coating delaminated after lithiation was completed. [Figure 2B] Photograph showing substantial expansion after full lithiation. [Figure 3A] Photograph showing the anode electrode prepared with cyclized PAN binder from a full pouch cell, no delamination of the anode coating is observed even after completion of lithiation. [Figure 3B]Photograph showing the anode electrode prepared with cyclized PAN binder from a full pouch cell, even after completion of lithiation, no delamination of the anode coating was observed due to the cyclized PAN binder acting like a superglue providing excellent structural stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The embodiments are described more fully below with reference to the accompanying drawings, which form a part hereof and which illustrate, by way of example only, certain exemplary embodiments. These embodiments are disclosed in sufficient detail to enable those skilled in the art to practice the disclosure. However, the embodiments may be embodied in many different forms and should not be construed as limited to the embodiments set forth herein. Thus, the following detailed description is not to be taken in a limiting sense.

[0013] Described herein are various embodiments of Si-based anodes and methods for making the same, which include a Si composite material as an active material component.

[0014] In some embodiments, an anode formulation configured to form an anode for use in an electrochemical energy storage device is described. The anode formulation includes a plurality of active material particles, a plurality of conductive carbon particles, and at least one polymer binder that undergoes a cyclization reaction when heated. The active material particles include Si composite particles, such as particles of Si-carbon composite or silicon oxide composite.

[0015] In some embodiments, an electrochemical energy storage device is described, which includes an anode, a cathode, and an electrolyte. The anode is made of a plurality of active material particles, conductive carbon particles, and at least one polymer binder that undergoes a cyclization reaction when heated. The active material particles include Si composite particles, such as Si-carbon composite or silicon oxide composite particles. The electrolyte may include a fluorinated carbonate.

[0016] Various embodiments of Si-based anodes including Si composite active materials are described herein. The use of Si composite materials, such as Si-carbon and Si-oxide composites, as the active material in the anode material provides a desired level of stability of the material compared to anode materials using pure Si as the active material. In embodiments where the Si composite material provides a core-shell structure (e.g., a Si core with a carbon or oxide shell), the outer shell material shields the Si particles from direct contact and exposure to the electrolyte. The use of Si composite materials, such as those with a core-shell structure, also allows for the expansion and contraction of silicon in the core-shell structure based on the porosity of the outer shell. This results in improved stability of the Si-based composite material compared to pure Si active materials.

[0017] The anode material formulation described herein includes a plurality of active material particles. At least some of the active material particles provided in the anode material are Si composite particles. In some embodiments, all of the active material particles are Si composite particles. When all active material particles present in the anode are Si composite particles, the Si composite particles may all be of the same type (e.g., all Si composite particles are Si-carbon particles), or the Si composite particles may be composed of two or more different types of Si composite particles (e.g., some Si composite particles are Si-carbon particles, while other Si composite particles are silicon oxide particles). In embodiments in which the plurality of active material particles includes both Si composite particles and non-Si composite particles, the Si composite particles can all be of one type, or can be two or more types of Si composite particles. The non-Si composite particles may be one or more suitable types of active materials that are not Si composite materials. In some embodiments, the non-Si composite particles included in the anode material are pure silicon particles.

[0018] Any suitable Si composite material can be used for the Si composite particles included in the anode materials described herein. In some embodiments, the Si composite particles are Si-carbon composite materials, such as carbon-coated Si particles. In some embodiments, silicon oxide (SiO x ) is used. The Si composite may be an alloy of Si with an inert metal or nonmetal. Other examples of Si composite materials suitable for use in the embodiments described herein are graphene-silicon composites, graphene oxide-silicon-carbon nanotubes, silicon-polypyrrole, and composites of nano- and micron-sized silicon particles. As mentioned above, any combination of Si composite materials may be used in the anode material, or only a single Si composite material may be used.

[0019] In some embodiments, the Si composite material generally has a core-shell structure, and the core is primarily or exclusively silicon. The shell may generally be a non-silicon material that acts as a protective coating around the silicon material core. For example, the Si composite material may be a Si-carbon material with a core-shell structure, such that carbon forms a shell around the silicon material core. For example, in the Si-carbon composite example described above, the core may contain some carbon in addition to the main silicon core, and the shell may contain some silicon in addition to the main carbon shell.

[0020] In some embodiments, the Si composite particle content of the anode material is from about 10% to about 90% by weight of the anode material, such as from about 20% to about 80% by weight or from about 50% to about 80% by weight. In some embodiments, the Si composite particles present in the anode composite material may have a size ranging from about 1 nm to about 100 μm.

[0021] The anode material formulation described herein includes at least one polymer binder that undergoes a cyclization reaction when heated. The polymer component of the anode material typically acts as a binder material and provides conductivity to the anode material. In some embodiments, the at least one polymer is polyacrylonitrile (PAN). Other polymer materials in addition to PAN may be included in the anode material as needed. In some embodiments, the at least one polymer binder included in the anode material comprises about 10% to about 40% by weight of the anode material. As previously mentioned, PAN is used as a polymer binder that forms an elastic and robust film that allows for controlled fragmentation / crushing of silicon composite particles in the binder matrix. However, the role of the cyclized PAN binder is different for Si composite materials, assuming that particle level crushing is not an issue. The cyclized PAN binder acts as a conductive matrix that provides a pathway for electrons and also aids in the formation of an SEI layer in organic solvents, such as carbonate-based electrolyte compositions. The prior art teaches the use of cyclized PAN binders and ionic liquid-based electrolytes that allow for pure silicon metal materials. However, the use of organic solvent-based electrolytes has been shown to degrade battery performance. In contrast, the present disclosure reports the use of Si composite materials, conductive carbon, and cyclized PAN polymer binders without an ionic liquid-based electrolyte composition.

[0022] In some embodiments where PAN is used as part or all of the polymer binder component of the anode material, the anode material is prepared and / or processed in such a manner that the PAN becomes cyclized PAN. That is, in the final form of the anode material, the polymer binder comprises cyclized PAN. Any method of preparing and / or processing the anode material to cyclize the PAN may be used. In some embodiments, the anode material is heated within a range of about 200° C. to about 600° C. to cyclize the PAN polymer binder component. In some embodiments, the anode material is heated to a temperature above 230° C. to effect this cyclization. In some embodiments, a temperature range between 240° C. and 400° C. is used.

[0023] The anode material formulation described herein includes a plurality of conductive carbon particles, such as conductive carbon nanoparticles. When conductive carbon particles are included in the anode material, they may be present in a range of about 0.1% to about 5% by weight. Any suitable conductive nanoparticles may be used, including, but not limited to, vapor grown carbon fibers (VGCF), carbon black, and carbon nanotubes. Such conductive nanoparticles may increase the conductivity of the anode material.

[0024] In addition to the Si composite particles, conductive carbon particles, and polymer binder already described, the anode material described herein may include other materials typically suitable for use in anode materials. For example, non-Si composite particles may be included in the anode material, as already described. Other materials that may be present in the anode material include, but are not limited to, sulfur, hard carbon, graphite, tin, and germanium particles. When present in the anode material, these additional materials may be present in a range of about 0.1% to about 60% by weight of the anode composite material, for example, in a range of about 10% to about 60% by weight.

[0025] Other additional components that may be included in the anode material include acid binders. Acid binders that may be included in the anode slurry used to make the anode material may include, for example, oxalic acid, citric acid, maleic acid, tartaric acid, and 1,2,3,4-butanetetracarboxylic acid. Acid binders can be used to improve dispersion and adhesion properties. When used in the anode material, acid binders may be present in the anode formulation in a range of about 0.01% to about 2% by weight.

[0026] The anode comprising the Si composite material described herein can be incorporated into an electrochemical energy storage device. The electrochemical energy storage device comprises the anode, cathode, and electrolyte described herein. In some embodiments, the electrochemical energy storage device is a lithium secondary battery. In some embodiments, the secondary battery is a lithium battery, a lithium ion battery, a lithium-sulfur battery, a lithium-air battery, a sodium ion battery, or a magnesium battery. In some embodiments, the electrochemical energy storage device is an electrochemical cell, such as a capacitor. In some embodiments, the capacitor is an asymmetric capacitor or a supercapacitor. In some embodiments, the electrochemical cell is a primary cell. In some embodiments, the primary cell is a lithium / MnO2 battery or a Li / poly(carbon monofluoride) battery.

[0027] Cathodes suitable for use in electrochemical energy storage devices include, but are not limited to, lithium metal oxides, spinels, olivine, carbon-coated olivine, LiCoO2, LiNiO2, LiMn 0.5 Ni 0.5 O2, LiMn 0.3 Co 0.3 Ni 0.3 O2, LiMn2O4, LiFeO2, LiNi x Co y Met z O2, A n’ B2(XO4)3, vanadium oxide, lithium peroxide, sulfur, polysulfides, lithium carbon monofluoride (LiCF x or a mixture of any two or more thereof, wherein Met is Al, Mg, Ti, B, Ga, Si, Mn, or Co; A is Li, Ag, Cu, Na, Mn, Fe, Co, Ni, Cu, or Zn; B is Ti, V, Cr, Fe, or Zr; X is P, S, Si, W, or Mo; and 0≦x≦0.3, 0≦y≦0.5, and 0≦z≦0.5, and 0≦n 1 According to some embodiments, the spinel has the formula Li 1+x Mn2-z Met''' y O 4-m X' n In another embodiment, the olivine is a spinel manganese oxide of the formula LiFePO4 or Li 1+x Fe 1z Met” y PO 4-m X' n where Met″ is Al, Mg, Ti, B, Ga, Si, Ni, Mn, or Co; X′ is S or F; and 0≦x≦0.3, 0≦y≦0.5, 0≦z≦0.5, 0≦m≦0.5, and 0≦n≦0.5.

[0028] In some embodiments, the electrolyte component of an electrochemical energy storage device includes an aprotic organic solvent system, a metal salt, and at least one electrolyte additive.

[0029] In some embodiments, the aprotic organic solvent component of the electrolyte is selected from open chain or cyclic carbonates, carboxylate esters, nitriles, ethers, sulfones, sulfoxides, ketones, lactones, dioxolanes, glymes, crown ethers, siloxanes, phosphate esters, phosphites, mono- or polyphosphazenes, or mixtures thereof, in the range of 20% to 90% by weight.

[0030] In some embodiments, the metal salt component of the electrolyte is a lithium salt in the range of 10% to 30% by weight. Various lithium salts are available, for example, Li(AsF6);Li(PF6);Li(CF3CO2);Li(C2F5CO2);Li(CF3SO3);Li[N(CP3SO2)2];Li[C(CF3SO2)3];Li[N(SO2C2F5)2];Li(ClO4);Li(BF4);Li(PO2F2);Li[PF2(C2O4)2];Li[PF4C2O4];Lithium alkyl fluorophosphates;Li[B(C2O4)2];Li[BF2C2O4];Li2[B12 Z 12-j H j ];Li2[B 10 X 10-j’ H j’ or a mixture of any two or more of these, wherein Z is independently at each occurrence a halogen, j is an integer from 0 to 12, and j′ is an integer from 1 to 10, may be used inclusive.

[0031] In some embodiments, the electrolyte additive is a compound containing at least one unsaturated carbon-carbon bond, a carboxylic acid anhydride, a sulfur-containing compound, a phosphorus-containing compound, a boron-containing compound, a silicon-containing compound, or a mixture thereof, in the range of 0.1% to 10% by weight.

[0032] In some embodiments where the electrochemical energy storage device is a secondary battery, the secondary battery may further include a separator separating the positive and negative electrodes. The separator for lithium batteries is often a microporous polymer film. Examples of polymers for forming the film include polypropylene, polyethylene, nylon, cellulose, nitrocellulose, polysulfone, polyacrylonitrile, polyvinylidene fluoride, polybutene, or a copolymer or blend of any two or more such polymers. In some cases, the separator is a microporous polyolefin separator that has been treated with an electron beam. The electron treatment can increase the deformation temperature of the separator, thus increasing its thermal stability at high temperatures. Additionally or alternatively, the separator can be a shutoff separator. The shutoff separator may have a trigger temperature greater than about 130° C. to allow the electrochemical cell to operate at temperatures up to about 130° C.

[0033] Referring to FIG. 1 , a flow diagram illustrating an embodiment of a method 100 for preparing an anode material described herein includes step 110 of mixing silicon composite particles, conductive carbon particles, and a polymer binder together to form a mixture, step 120 of adding a solvent to the mixture and coating the mixture onto a copper current collector, and step 130 of removing the solvent from the coating and subjecting the coated current collector to a heat treatment.

[0034] At step 110, the silicon composite particles, conductive carbon particles, and at least one polymer binder are mixed together to form a mixture. Any technique for mixing these materials together can be used, but in some embodiments, mechanical mixing is used. For example, the components can be mixed together by ball milling the solids at low rpm.

[0035] At step 120, a solvent is added to the mixture to disperse the active material particles. Any suitable solvent can be used in any suitable amount. In some embodiments, the solvent is anhydrous NMP. Other suitable solvents include, but are not limited to, N,N-dimethylformamide (DMF), dimethylsulfone (DMSO2), dimethylsulfoxide (DMSO), ethylene carbonate (EC), and propylene carbonate (PC). The solvent can be mixed with the mixture of silicon composite particles, conductive carbon particles, and polymer binder for any suitable length of time, for example, about 12 hours. Solvent mixing can be performed using high shear centrifugal mixing or using a stir bar in a glass vial.

[0036] Step 120 further includes coating the slurry mixture onto a current collector. The material of the current collector can be any suitable current collector material, for example, copper. The coating step can be performed using any suitable technique and equipment, for example, a benchtop doctor blade coater.

[0037] In step 130, the solvent is removed from the material coated on the current collector and then the coated current collector is subjected to a heat treatment. Although this step is described as two separate operations, in some implementations it may be possible to remove the solvent from the coating as part of the heat treatment step. When the solvent is first removed, it may be removed by heating the coating at a temperature that is generally lower than the temperature used in the subsequent heat treatment step, but higher than the temperature required to remove the solvent from the coating. For example, in some embodiments, the solvent is removed from the coating by first subjecting the coated current collector to a temperature of about 60° C. (such as in a convection oven) to evaporate the solvent.

[0038] After solvent removal, step 130 continues with subjecting the coated current collector to a heat treatment. The heat treatment may include heating the coated current collector in an inert atmosphere to a temperature ranging from about 200° C. to about 600° C., for example, to about 330° C. in an inert argon gas atmosphere. The temperature may range from about 240° C. to about 400° C. The heat treatment step generally targets cyclization of the polymer component of the coating. As previously mentioned, the polymer component of the coating may be PAN. Cyclization of PAN is a process when nitrile bonds (C≡N) are converted to double bonds (C═N) due to crosslinking of the PAN molecules. This process results in ladder polymer chains of PAN fibers that are elastic but mechanically robust, thus allowing for controlled fragmentation of the silicon particles.

[0039] The present disclosure will be further illustrated with reference to the following specific examples, which are understood to be offered by way of illustration and are not meant to limit the scope of the following disclosure or claims. EXAMPLES

[0040] Silicon oxide composite materials were mixed with conductive carbon black and 150,000 MW (150K) PAN for the anodes of Examples 1 and 2, and with conductive carbon black and PVDF for the comparative anode by ball milling the solids at low rpm. The anode compositions are shown in Table 1 below. Using anhydrous NMP as the solvent, the C65 conductive carbon black additive was dispersed using centrifugal mixing, after which the silicon / PAN solids mixture was added to the dispersions of Examples 1 and 2, and the silicon / PVDF solids mixture was added for the comparative example. Each slurry was mixed overnight and coated onto a copper current collector using a benchtop doctor blade coater to produce a concentration of >3 mg / cm. 2 The anode electrode was dried at 60° C. to remove the NMP solvent.

[0041] Except for the comparative anode electrode containing a PVDF binder, the two anode electrodes containing the PAN binder of Examples 1 and 2 were then heat treated in an inert argon atmosphere at 330° C. During the heat treatment process, the PAN binder undergoes a cyclization process to convert the suspended nitriles (triple bonds) into conjugated nitrile groups.

[0042] [Table 1]

[0043] To understand the effectiveness of the cyclized PAN binder in providing both mechanical integrity and conductivity, a full pouch cell was constructed using a NMC811 cathode (4 mAh / cm 2 ) Table 2 compares the full cell data for the anode compositions shown in Table 1. Organic solvent-based electrolytes were used for all anode compositions listed in Table 1.

[0044] [Table 2]

[0045] 2 and 3 show the mechanical integrity of the anode electrode after lithiation is complete. Apparently the cyclized PAN binder provides strong mechanical strength compared to known binder systems.

[0046] Table 3 compares the measured electrochemical properties of the anode electrode to the NMC811 cathode. The cyclized PAN binder provides higher lithiation potential, whereas the PVDF binder performed poorly due to poor conductivity and poor mechanical strength.

[0047] [Table 3]

[0048] Thus, through the roll-to-roll anodic coating process, we are able to engineer the surface chemistry of silicon materials. The coating driven by the cyclized PAN polymer binder provides silicon with its mechanical strength, electrical conductivity, and chemical stability, addressing the main challenges.

[0049] While various embodiments have been shown and described in detail herein, it will be apparent to those skilled in the relevant art that various modifications, additions, substitutions, and the like can be made without departing from the spirit of the disclosure and are therefore deemed to be within the scope of the present disclosure as defined in the claims which follow.

Claims

1. 1. An anode formulation for forming an anode for use in an electrochemical energy storage device, comprising: a plurality of active Si composite material particles; A plurality of conductive carbon particles; and At least one polymeric binder that undergoes a cyclization reaction when heated. an anode formulation comprising:

2. The anode formulation of claim 1, wherein the Si composite material is a Si-carbon composite material.

3. 2. The anode formulation of claim 1, wherein the Si composite material is a silicon oxide material.

4. 10. The anode formulation of claim 1, wherein the plurality of Si composite material particles comprises particles ranging from about 1 nm to about 100 μm.

5. 10. The anode formulation of claim 1, wherein the at least one polymer binder comprises polyacrylonitrile.

6. 10. The anode formulation of claim 1, wherein the plurality of Si composite particles comprises about 10% to about 90% by weight of the anode formulation.

7. 10. The anode formulation of claim 1, wherein the plurality of conductive carbon particles comprises about 0.1% to about 5% by weight of the anode formulation.

8. 10. The anode formulation of claim 1, wherein the at least one polymer binder comprises from about 10% to about 40% by weight of the anode formulation.

9. 10. The anode formulation of claim 1, wherein the conductive carbon particles comprise nanoparticles of vapor grown carbon fibers (VGCF), carbon black, carbon nanotubes, or a mixture thereof.

10. 13. The anode formulation of claim 1, further comprising an acid binder comprising from about 0.01% to about 2% by weight of the anode formulation.

11. The anode formulation of claim 10, wherein the acid binding agent comprises oxalic acid, citric acid, maleic acid, tartaric acid, 1,2,3,4-butanetetracarboxylic acid, or mixtures thereof.

12. 1. An anode for use in an electrochemical energy storage device, comprising: Current collector having a coating comprising an active Si composite material, conductive carbon, and at least one cyclized polymer binder an anode.

13. 13. The anode of claim 12, wherein the at least one cyclized polymer binder is a cyclized polyacrylonitrile.

14. The anode of claim 12, wherein the Si composite material is a Si-carbon composite material.

15. The anode of claim 12 , wherein the Si composite material is a silicon oxide material.

16. 13. The anode of claim 12, wherein the conductive carbon comprises vapor grown carbon fiber (VGCF), carbon black, carbon nanotubes, or a mixture thereof.

17. The anode of claim 12 further comprising an acid binding agent.

18. an anode comprising an active Si composite material, conductive carbon, and a current collector having a coating comprising at least one cyclized polymer binder; A cathode, and Electrolytes containing fluorinated carbonates 1. An electrochemical energy storage device comprising:

19. 20. The electrochemical energy storage device of claim 18, wherein the Si composite material is a Si-carbon composite material.

20. 20. The electrochemical energy storage device of claim 18, wherein the Si composite material is a silicon oxide material.

21. 20. The electrochemical energy storage device of claim 18, wherein the at least one cyclized polymer binder comprises cyclized polyacrylonitrile.

22. 20. The electrochemical energy storage device of claim 18, wherein the cathode further comprises lithium metal oxide, spinel, olivine, carbon-coated olivine, vanadium oxide, lithium peroxide, sulfur, polysulfides, lithium carbon monofluoride, or mixtures thereof.

23. 20. The electrochemical energy storage device of claim 18, wherein the cathode further comprises a transition metal oxide material and an over-lithiated oxide material.

24. 20. The electrochemical energy storage device of claim 18, further comprising a porous separator separating the anode and the cathode from each other.

25. 1. A method of making an anode for use in an electrochemical energy storage device, comprising: a) mixing together active Si composite particles, conductive carbon particles, and at least one polymer binder that undergoes a cyclization reaction when heated to form a mixture; b) coating the mixture onto a current collector to form a coated current collector; and c) subjecting the coated current collector to a temperature treatment to cyclize the at least one polymeric binder. A method comprising:

26. 26. The method of claim 25, wherein subjecting the coated current collector to the temperature treatment comprises heating the coated current collector in an inert atmosphere to a temperature in the range of about 200° C. to about 600° C.

27. 27. The method of claim 26, wherein the coated current collector is heated to a temperature in the range of about 240°C to about 400°C.

28. After step a) and before step b), adding a solvent to the mixture to disperse the Si composite particles, conductive carbon particles, and at least one polymer binder. The solvent may be N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), dimethylsulfone (DMSO 2 ), dimethylsulfoxide (DMSO), ethylene carbonate (EC), and propylene carbonate (PC).

29. After step b) and before step c), removing the solvent from the mixture coated on the current collector.

30. The method of claim 28, further comprising:

30. 30. The method of claim 28, wherein step c) removes the solvent from the mixture coated on the current collector.

31. 26. The method of claim 25, wherein the size of the Si composite particles ranges from about 1 nm to about 100 μm.

32. 26. The method of claim 25, wherein the mixture formed in step a) comprises about 10% to about 90% by weight of Si composite particles.

33. 26. The method of claim 25, wherein the mixture formed in step a) comprises from about 10% to about 40% by weight of the at least one polymeric binder.

34. 26. The method of claim 25, wherein the mixture formed in step a) comprises about 0.1% to about 5% by weight of the conductive carbon particles.

35. 26. The method of claim 25, wherein the at least one polymeric binder is polyacrylonitrile.